Multiple familial trichoepitheliomas: a case report - N., Priyadharshini; Irri, Harini; R., Sathyanarayanan (International Journal of Research in Dermatology, 2021)
Trichoepithelioma is a rare benign adnexal tumor that differentiates towards the folliculo-sebaceous-apocrine unit (trichoblast). It may present as solitary non-familial lesion or multiple lesions as a part of autosomal dominant inherited syndrome known as multiple familial Trichoepithelioma. Multiple familial trichoepithelioma is a relatively rare, disfiguring, benign adnexal neoplasm diagnosed by centrofacial distribution of papules and nodules, positive family history, related histopathological findings and can rarely undergo malignant transformation. Treatment is mainly for cosmetic concern. Here we report a case who presented with multiple skin coloured facial papules and nodules, with a history of similar lesions in other family members. Dermoscopy and histopathology confirmed the diagnosis of trichoepitheliomas.